Permasalahan Cita-cita Anak yang Menyebabkan Kelangkaan Petani Masa Depan - Albertus Galih Pamuji (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2017)
Every child has a dream. Nowadays, the ideals of children tend not to be interested in the agricultural sector it becomes a big problem. If young generations are not interested in agriculture then it can cause problems in the future. The profession as a farmer is considered primitive and does not guarantee welfare. In order to attract the interest of children, it is necessary to improve development in the agricultural sector, so that farmers can gain prosperity. Schools, teachers, and parents hold important roles to support children so that they have the passion and willingness to understand the agriculture sector. It needs early effort to introduce to children anything about agriculture so that the love and tolerance of children can grow. Giving scholarships to children for continuing their education can also be done to increase the number of farmers in the future.